2022
DOI: 10.3920/wmj2021.2683
|View full text |Cite
|
Sign up to set email alerts
|

The potential for aflatoxin predictive risk modelling in sub-Saharan Africa: a review

Abstract: This review presents the current state of aflatoxin risk prediction models and their potential for value actors throughout the food chain in sub-Saharan Africa, with a specific focus on improving smallholder farmer management practices. Several empirical and mechanistic models have been developed either in academic research or by private sector aggregators and processors in high-income countries including Australia, the USA, and Southern Europe, but these models have been only minimally applied in sub-Saharan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Likewise, in Temba et al (2021), low rainfall combined with high temperatures increase the chances of aflatoxin contamination in maize which proves the case in the study sites. Equally, in Keller et al (2022), the evolving climatic conditions in sub -Saharan Africa, Kenya included, are conducive for aflatoxin production. As stated by Kangethe et al (2017), Nandi and Makueni are hot spot regions for aflatoxin contamination in maize and fall in the same agro ecological zones of lower humid highlands to upper midlands, and upper high land zones (LH2, LH3, LM4, LH5), (UM3 UM4).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in Temba et al (2021), low rainfall combined with high temperatures increase the chances of aflatoxin contamination in maize which proves the case in the study sites. Equally, in Keller et al (2022), the evolving climatic conditions in sub -Saharan Africa, Kenya included, are conducive for aflatoxin production. As stated by Kangethe et al (2017), Nandi and Makueni are hot spot regions for aflatoxin contamination in maize and fall in the same agro ecological zones of lower humid highlands to upper midlands, and upper high land zones (LH2, LH3, LM4, LH5), (UM3 UM4).…”
Section: Discussionmentioning
confidence: 99%
“…Such data would be needed to recalibrate the empirical part of the model. The Partnership for Aflatoxin Control in Africa is currently collecting data and establishing an information management system, which could help provide relevant warning (Keller et al., 2021).…”
Section: Case Studies Illustrating the Potential Contributions Of Big...mentioning
confidence: 99%
“…Several models are amenable for use in Africa. Keller et al (2021) listed 15 methods for mycotoxin prediction that would be suitable for application in sub-Saharan Africa, that is, AFLA-maize, AFLA-maize + carryover, AFLApistachio, APHLIS+, APSIM+ Risk Model, AVHRR-based, CROPGRO, drought index (ARID), Maxent2, multilevel modeling, multivariate regression, risk in storage, spatial Poisson profile regression, and stacked Gaussian. Their accuracies varied between 54% and 99% for 10 methods (with the remaining ones being not predictive, future projections, or unvalidated).…”
Section: Mycotoxins and Fungal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Satelliteacquired databases, including the normalized difference vegetation index (NDVI), have been previously used in studies evaluating mycotoxins in European wheat and led to higher mycotoxin model accuracy (Wang et al, 2022). Several studies have shown significant correlations among climate, soil properties, NDVI, and agricultural management practices with AFL contamination in Africa, as reviewed by Keller et al (2022). AFL studies conducted in Eastern and Western Kenya (Mutiga et al, 2014) support the utility of remote-sensing data such as NDVI, rainfall, and soil properties (such as organic carbon content, pH, total exchangeable bases, salinity, texture, and soil type) to accurately predict AFL contamination (Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%